2011
DOI: 10.1519/jsc.0b013e3181e86132
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Traditional and Ballistic Squat Exercise With Vertical Jumping and Maximal Sprinting

Abstract: The purpose of this study was to quantify the magnitude of the relationship between vertical jumping and maximal sprinting at different distances with performance in the traditional and ballistic concentric squat exercise in well-trained sprinters. Twenty-one men performed 2 types of barbell squats (ballistic and traditional) across different loads with the aim of determining the maximal peak and average power outputs and 1 repetition maximum (1RM) values. Moreover, vertical jumping (countermovement jump test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
4
25
0
1
Order By: Relevance
“…As would be expected, semi-professional sprinters also displayed significantly quicker 20 m sprint times (2.85 ± 0.13 s) and greater jump height (53.6 ± 4.9 cm). 11 Because much of the sprint running performed in team sports, and in particular cricket, is over a very short distance, the ability to increase velocity in the first few ground contacts of the acceleration phase may be considered more important to team sport performance than maximal velocity running. These first few ground contacts consist mainly of concentric muscle actions and propulsive forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As would be expected, semi-professional sprinters also displayed significantly quicker 20 m sprint times (2.85 ± 0.13 s) and greater jump height (53.6 ± 4.9 cm). 11 Because much of the sprint running performed in team sports, and in particular cricket, is over a very short distance, the ability to increase velocity in the first few ground contacts of the acceleration phase may be considered more important to team sport performance than maximal velocity running. These first few ground contacts consist mainly of concentric muscle actions and propulsive forces.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bosco et al 8 found a very strong inverse relationship between CMJ height and 30 m sprint time (r = -0.93, p<0.01), similar to the correlation between the same variables found by Hori et al 9 (r = -0.69, p<0.01). Lopez-Sigovia et al 10 found an inverse correlation between CMJ height and 20 m sprint time of r = -0.54 (p<0.05), and Requena et al 11 found a correlation between the same variables of r = -0.47 (p<0.05). Nesser et al 12 found a moderate inverse correlation of r = -0.464 (p<0.05) between vertical jump height and 40 m sprint time.…”
Section: Introductionmentioning
confidence: 97%
“…This concentric muscular action needs to be forceful and rapid enough to achieve maximal height. Initial fast and forceful concentric muscle actions need to be at maximum muscular effort as in a ballistic squat to achieve the greatest possible height (29). The greatest amount of force production will be determined by muscle fiber type (type II versus type I), neurological control and activation (rate coding, recruitment, and inter-and intramuscular coordination), Ca +2 phosphorylation on myosin regulatory light chains, muscle cross-sectional area, muscle length, joint angle, contraction velocity, joint angular velocity, strength-to-mass ratio, and fiber arrangement (1,28,36).…”
Section: Muscular Actionsmentioning
confidence: 99%
“…Although there may be minimal relationship between absolute squat 1RM and CMJ, there is a suggestion that relative 1RM squat performance may have more of a role in predicting CMJ height (29). Practitioners also need to have athletes perform exercises with a resistance that will recruit the desired muscle fibers (types IIa and IIx) required by using heavy loaded exercises, such as squats.…”
Section: Application Of the Cmjmentioning
confidence: 99%
“…M uscular power has been shown to correlate with performance in athletic movements, such as jumping, sprinting, and agility tests, and with playing level in a number of sports (3, 10,17,32,34). Therefore, the efficient development of muscular power is a high priority for strength and conditioning programmes.…”
Section: Introductionmentioning
confidence: 99%